(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The increasing water supply challenges have become a significant problem; as severe water shortages have been seen worldwide. While the MBR has made great development and has shown to be a viable option for waste water treatment, conventional MBRs still have numerous weaknesses, which is why the MBRs for waste water processing technologies have been incorporated. This article aims to combine the current state of the art for the integrated MBR process with other wastewater treatment systems and offer a consolidated analysis of the sustainability of the treatment process. This article looks at the potential applications of various types of MBR. It aims to prepare the path for the future deployment of improved MBR as a potential wastewater treatment technology. The improvement in wastewater in integrated MBR will reduce emissions and provide a new energy and nutrient source. The improved MBR also enables the recovery of energy and nutrients ecologically and economically feasible.